INDUSTRY PREPARATION IN CEPER KLATEN ON SOCIETY 5.0 - Vivin Zulfa Atina; Anas Yusuf Mahmudi; Hamid Abdillah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Based on observations of the Industry in Ceper Klaten, several industries still apply manual systems in their work. This also relates to the human resources and technology they have. This is contrary to the demands of the times, which are all digital and automatic. Research on the readiness of Society 5.0 employees as a means of campaigning employees about existing technological developments. This method is limited to the definition of a sample survey which aims to test the previously formulated hypotheses (testing research). The results of this test indicate that overall all analyzed pathways have a significant relationship, as seen from the probability level (P) less than 0.05. This significant relationship is also supported by Understanding CR > 1.96 in all analyzed pathways.